The Influence of Parents' Education Level on Motivation and Learning Outcomes of Madrasah Ibtidaiah Students: Pengaruh Tingkat Pendidikan Orang Tua Terhadap Motivasi dan Hasil Belajar Siswa Madrasah Ibtidaiah - Amaliyah, Dinda Ilmi Rizqi; Udin, Bahak (Indonesian Journal of Education Methods Development, 2021)
The problem raised in this study is whether there is a positive influence of the level of parental education on the motivation and learning outcomes of students in grade 5 MI Asasul Huda Kepuh Kemiri. With parents who have good backgrounds, it is hoped that students will be able to get good and maximum learning outcomes at school. Education is a very important aspect to improve students' abilities and skills. The purpose of this study was to determine the effect of the education level of the tau people on the motivation and learning outcomes of students in grade 5 MI Asasul Huda Kepuh Kemiri. To achieve the objectives of this study, the researcher used a quantitative method with a questionnaire/questionnaire which was distributed to all 5th grade students of MI Asasul Huda Kepuh Kemiri, totaling 36 students. However, due to the constraints of some students who could not fill out the questionnaire/questionnaire, in the end the researcher only got 31 samples. There are several stages that researchers must go through in research, namely interviews with homeroom teachers to get real problems, formulating hypotheses, making research instruments, collecting data, analyzing data and drawing conclusions. The results showed that the education level of parents had no effect on the motivation and learning outcomes of grade 5 students. This was evidenced by the results of the analysis of the effect of the significance value obtained from the education level of parents with a motivation of 0.228 > 0.05, with a t count of 1.232 and t table 2,045 which resulted in H0 being accepted and Ha rejected, while the education level of parents with learning outcomes obtained a significance of 0,528 > 0,05 and t count -,639 and t table 2,045 which resulted in H0 being accepted and Ha rejected. Keywords - Education Level Parents, Motivation, Learning Outcomes.